Cassava starch/bacterial cellulose-based bioplastics with Zanthoxylum acanthopodium (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Gea S, Pasaribu KM, Sarumaha AA, Rahayu S. 2022. Cassava starch/bacterial cellulose-based bioplastics with Zanthoxylum acanthopodium. Biodiversitas 23: 2601-2608. The use of conventional plastics has become one of the biggest environmental problems because of their difficulties in decomposing. Bioplastics are plastics that are decompose easily in nature as they are naturally sourced. The purpose of this research was to create antimicrobial bioplastics from cassava starch with the addition of bacterial cellulose (BC) as a reinforcement material and Zanthoxylum acanthopodium (andaliman) as an antibacterial agent. Furthermore, this study determines the optimal concentration of BC and the antibacterial effect of Z. acanthopodium extract in bioplastics produced by the solution casting method. The addition of BC to bioplastics changed the properties of bioplastics, according to FTIR, XRD, TGA, SEM, and tensile strength analysis. Mechanical analysis showed an increase in tensile strength with higher amount of BC. The best tensile strength was observed in CS2BCA sample (2.34 MPa). The antibacterial test of bioplastic samples showed good inhibition zone (10.8 mm) against Bacillus cereus.
Keywords: Antibacterial, bacterial cellulose, bioplastics, cassava starch, Zanthoxylum acanthopodium